Electromigration tuning of the voltage modulation depth in YBa2Cu3O7−δ nanowire-based SQUIDs. (24th August 2021) - Trabaldo, E; Garibaldi, A; Lombardi, F; Bauch, T
Abstract: Oxygen electromigration applied to a YBa2 Cu3 O 7 − δ nanowire can be used to tune its electrical properties. Here, we apply electromigration to YBCO nanowire-based superconducting quantum interference devices (SQUIDs) and study its effect on the voltage modulation depth of the devices. Using a dc electromigration current we replenish the oxygen of the weak links, improving the critical current symmetry of the SQUIDs. AC current electromigration is used to reduce the doping level of the weak links, thus reducing their critical current and increasing differential resistance. Both type of electromigration processes are found to improve the SQUIDs performance, although the best results are obtained with ac biased electromigration, which improved the voltage modulations of the SQUIDs by a factor as high as 8. This procedure can be instrumental to fine tune ex-situ the properties of superconducting electronics where a large number of weak links are required.